Algae-Assisted Microbial Desalination Cell: Analysis of Cathode Performance and Desalination Efficiency Assessment - David Ewusi-Mensah (MDPI AG, 2021)
Algae-assisted microbial desalination cells represent a sustainable technology for low-energy fresh water production in which microalgae culture is integrated into the system to enhance oxygen reduction reaction in the cathode chamber. However, the water production (desalination rate) is low compared to conventional technologies (i.e., reverse osmosis and/or electrodialysis), as biocathodes provide low current generation to sustain the desalination process. In this sense, more research efforts on this topic are necessary to address this bottleneck. Thus, this study provides analysis, from the electrochemical point of view, on the cathode performance of an algae-assisted microbial desalination cell (MDC) using Chlorella vulgaris. Firstly, the system was run with a pure culture of Chlorella vulgaris suspension in the cathode under conditions of an abiotic anode to assess the cathodic behavior (i.e., cathode polarization curves in light-dark conditions and oxygen depletion). Secondly, Geobacter sulfurreducens was inoculated in the anode compartment of the MDC, and the desalination cycle was carried out. The results showed that microalgae could generate an average of 9–11.5 mg/L of dissolved oxygen during the light phase, providing enough dissolved oxygen to drive the migration of ions (i.e., desalination) in the MDC system. Moreover, during the dark phase, a residual concentration of oxygen (ca. 5.5–8 mg/L) was measured, indicating that oxygen was not wholly depleted under our experimental conditions. Interestingly, the oxygen concentration was restored (after complete depletion of dissolved oxygen by flushing with N2) as soon as microalgae were exposed to the light phase again. After a 31 h desalination cycle, the cell generated a current density of 0.12 mA/cm2 at an efficiency of 60.15%, 77.37% salt was removed at a nominal desalination rate of 0.63 L/m2/h, coulombic efficiency was 9%, and 0.11 kWh/m3 of electric power was generated. The microalgae-assisted biocathode has an advantage over the air diffusion and bubbling as it can self-sustain a steady and higher concentration of oxygen, cost-effectively regenerate or recover from loss and sustainably retain the system’s performance under naturally occurring conditions. Thus, our study provides insights into implementing the algae-assisted cathode for sustainable desalination using MDC technology and subsequent optimization.